2013
DOI: 10.5176/2339-5060_1.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Ionic Liquid 1-Butyl-3- Methylimidazolium Bistrifluoromethane- Sulfonamide on Nucleophile Reactivity in Unimolecular Solvolysis Reactions Involving Carbocationic Intermediates

Abstract: Solvolysis studies of pivaloyl triflate were carried out in the ionic liquid 1-butyl-3-methylimidazolium bistrifluoromethanesulfonamide with various cosolvents. Reaction solutions were analyzed by 1 H NMR and the relative amounts of substitution and elimination products measured. It was found that regardless of cosolvent, increasing the ionic liquid:cosolvent ratio leads to increased elimination product. The rate of increase, however, is dependent on the identity of the cosolvent. Kamlet-Taft solvatochromic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Our preliminary studies have shown that increasing the mole fraction of IL in an IL:alcohol dual solvent system increases the favorability of the elimination pathway vs. nucleophilic attack [15,16]. It was observed that nearly all IL cosolvents caused an increase in the favorability of the elimination pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our preliminary studies have shown that increasing the mole fraction of IL in an IL:alcohol dual solvent system increases the favorability of the elimination pathway vs. nucleophilic attack [15,16]. It was observed that nearly all IL cosolvents caused an increase in the favorability of the elimination pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The triflate derivative of pivaloin, 1, was prepared from the corresponding alcohol as previously described [15]. The ionic liquid, 1-butyl-3-methylimidazolium bistrifluoromethane-sulfonamide, [C 4 C 1 im][NTf 2 ], was prepared and dried as previously described [12] [18].…”
Section: Generalmentioning
confidence: 99%